Product Planning for Soda Can Lids Using the Quality Function Deployment (QFD) Method - Shandy Listian Yuliady; Wahyu Ardiansyah; Khusna Dwijayanti (Journal of Industrial Engineering and Halal Industries, 2026)
The carbonated beverage industry continues to grow in line with the increasing practical lifestyle of modern society. One of the main challenges in the packaging of soda products is the inability of the lid of the cans to maintain carbonation pressure after opening, which leads to a decrease in taste quality and consumer experience. This research aims to design an innovative soda can lid that preserves carbonation using the Quality Function Deployment (QFD) method. Data was collected through questionnaires distributed to 10 consumers to identify primary needs. House of Quality analysis revealed that product precision, ease of use, and material safety were the top priorities. The proposed design incorporates food-grade HDPE, ergonomic form, and a seal system to prevent leakage. The concept also emphasizes one-handed usability and aesthetic integration with packaging. The QFD approach effectively translates consumer needs into actionable technical specifications, and the final design is expected to enhance consumer satisfaction and loyalty.